Strategi Guru Tahfidz dalam Meningkatkan Hafalan Santri di Halaqoh Tahfidz Qur’an Masjid Al Ikhlas Koto Mandakek Kota Pariaman - Indraeni, Syadza Alzahra; Wiza, Rahmi (YASIN, 2025)
This study is motivated by the limited scholarly attention given to the strategies employed by tahfidz teachers within mosque-based halaqoh, despite the significant impact of such practices on the quality of students’ Qur’anic memorization, particularly in non-formal educational settings like mosques. Amid the rising number of Qur’an memorizers in Indonesia, many students continue to struggle with retaining their memorization and correcting makhraj. The objective of this research is to analyze the strategies used by tahfidz teachers to enhance students’ Qur’anic memorization at the Halaqoh Tahfidz Qur’an of Al-Ikhlas Mosque, Koto Mandakek, Pariaman City. This study employs a qualitative descriptive method, involving participants that include the halaqoh leader, one tahfidz teacher, and four students selected through purposive sampling. Data collection techniques comprise observation, in-depth interviews, and documentation. The findings reveal that the tahfidz teacher implements strategies such as identifying students’ characteristics, formulating learning objectives, applying the talaqqi-sima’i method, tikrar, group murojaah, and conducting participatory and continuous memorization assessments. These strategies have proven effective in gradually and comprehensively improving students’ memorization. This success is influenced by the teacher’s active engagement and adaptive approach tailored to each student’s individual needs. The findings imply that appropriate instructional strategies can strengthen tahfidz programs in non-formal education settings and foster the development of a generation of excellent Qur’an memorizers.